Associations Between Cognitive and Gait Performance During Single- and Dual-Task Walking in People With Parkinson Disease. Issue 6 (1st June 2014) - Stegemöller, Elizabeth L.; Wilson, Jonathan P.; Hazamy, Audrey; Shelley, Mack C.; Okun, Michael S.; Altmann, Lori J.P.; Hass, Chris J.
Abstract : Background: Cognitive impairments in Parkinson disease (PD) manifest as deficits in speed of processing, working memory, and executive function and attention abilities. The gait impairment in PD is well documented to include reduced speed, shortened step lengths, and increased step-to-step variability. However, there is a paucity of research examining the relationship between overground walking and cognitive performance in people with PD. Objective: This study sought to examine the relationship between both the mean and variability of gait spatiotemporal parameters and cognitive performance across a broad range of cognitive domains. Design: A cross-sectional design was used. Methods: Thirty-five participants with no dementia and diagnosed with idiopathic PD completed a battery of 12 cognitive tests that yielded 3 orthogonal factors: processing speed, working memory, and executive function and attention. Participants completed 10 trials of overground walking (single-task walking) and 5 trials of overground walking while counting backward by 3's (dual-task walking). Results: All gait measures were impaired by the dual task. Cognitive processing speed correlated with stride length and walking speed. Executive function correlated with step width variability. There were no significant associations with working memory. Regression models relating speed of processing to gait spatiotemporal variables revealed that including dual-task costs in the model significantly improved the fit of the model. Limitations: Participants with PD were tested only in the on-medication state. Conclusions: Different characteristics of gait are related to distinct types of cognitive processing, which may be differentially affected by dual-task walking due to the pathology of PD.